KOMPETENSI KEPRIBADIAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KECERDASAN SPIRITUAL SISWA DI SEKOLAH MENENGAH PERTAMA ISLAM TERPADU AL-MUTHMAINNAH KOTA JAMBI: Penelitian kualitatif - Sumirah; Solihin; Idarianty (STKIP Subang, 2024)
This study aims to find out: 1. The personality competence of Islamic Religious Education teachers in improving students' spiritual intelligence; 2. Efforts of Islamic Religious Education teachers in improving students' spiritual intelligence; 3. Factors that inhibit Islamic Religious Education teachers in increasing students' spiritual intelligence. The type of research used in this study is qualitative research. The data collection technique of this research uses observation, interviews, and documentation. The data analysis technique uses data reduction, data presentation, and drawing conclusions and verification. In testing the validity of the data, data triangulation is used. The results of the study were: 1. The personality competence of Islamic Religious Education teachers can be categorized as good, because it has met all the indicators contained in the teacher's personality competence, such as a steady and stable personality, mature, wise and wise, authoritative and polite, noble character and an example for students. 2. Efforts made by Islamic Religious Education teachers in schools, including being an example for students, giving advice to students, the habit of praying before and after studying, the habit of praying in congregation, the habit of reading the Qur'an, yasinan activities every Friday, infaq and sodaqoh activities and involving students in religious activities at school. 3. Factors that inhibit Islamic Religious Education teachers in schools, including students, family environment, and community environment.